Eficacia de procesos de esterilización en odontología - Yuquilema Huebla, Robert Tomas (2022)
ABSTRACT Sterilization is a process through which the it is possible the total destruction of microorganisms present in a certain material; this bibliographic review was carried out with the purpose of analyzing the effectiveness of sterilization processes in the dental field, which was carried out from the search for academic scientific publication, extracting certain information from different databases such as: Google Scholar, PubMed, Elsevier, Scielo, Scopus establishing the exclusion and inclusion criteria, average citation count (ACC), impact factor of the journal that publishes the article through Scimago Journal Ranking (SJR), after analysis and classification, it was obtained a total of 54 articles for review. Subsequently, when analyzing the chosen articles, a variety of sterilization processes were established for the instruments, which are: ultrasound, plasma technology, ionization, ultrasound, ethylene oxide gas, dry heat sterilizer and autoclave, however, due to its mechanism of action it can be established that the autoclave sterilization method is the most effective and adequate method for the elimination of microorganisms present in dental instruments. The effectiveness was compared, and it was found that the autoclave was the most effective method, by following a standard technical configuration a practical result can be obtained at 134°C for 18 minutes or 121- 132°C for 60 minutes, which in the dental field is very important because the working time is optimized, and the integrity and time-life of the instruments are guaranteed. Keywords: sterilization, autoclave, dental instruments, methods, dentistry. Reviewed by: Gabriela de la Cruz F. Msc ENGLISH PROFESSOR C.C. 0603467929